PENGARUH MODIFIKASI PAPAN PANTUL PESERTA DIDIK PUKULAN FOREHAND DRIVE DAN BACKHAND DRIVE - Rubiyanto, Dwi; Kresnadi, Hery; Puspa, Fitiana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractTo be able to optimize the way of hitting the backhand drive researchers try to see the conditions and circumstances as well as take advantage of school facilities. In this case the researcher will carry out the research of table tennis by playing bouncing the ball to bounce board. When the ball is reflected onto the bounce board it will be more controlled. The purpose of this research is to know the effect of modification of the bounce board aids of students of MTsN 1 Pontianak on forehand and backhand punch in table tennis game. In this study the researchers used a true experimental design form. the overall ability that forehand and backhand capabilities during the pre-test in the control group was found to average = 10 and 9 with standard deviation = 18.29 and 11.51. While in the experimental group obtained averages = 15.97 and 11.77 with standard deviation = 31.17 and 20.41. The ability of forehand and backhand strikes during the post-test in the control group obtained mean = 14.43 and 9.2 with standard deviation = 24.65 and 15.63. While in the experimental group obtained mean = 31.7 and 20.77 with standard deviation = 40.13 and 30.61. Keywords: Modifications, Boards, Table Tennis